Determination of phytoconstituents of n-hexane extract of leaves of Morus nigra and evaluation of their effects on biochemical and histopathological parameters in paracetamol intoxicated mice liver - Tauqeer Hussain Mallhi; Muhammad Imran Qadir; Yusra Habib Khan (Universidade de São Paulo, 2018)
In-vitro investigation of Morus nigra L. (Moraceae) has demonstrated the evidence of several antioxidant compounds. Current study was aimed to determine the phytoconstituents and hepatoprotective potential of n-hexane extract of Morus nigra. Swiss albino mice were divided into five groups: normal control, paracetamol control, silymarin control, 250 mg/kg p.o. extract for 7 days plus paracetamol 3 h later, 500 mg/kg p.o. extract for 7 days plus paracetamol 3 h later. Serum levels of liver enzymes and total bilirubin were assessed and compared between the groups by using one-way ANOVA to confirm hepatoprotective activity. HPLC analysis revealed the presence quercetin, oleanolic acid, luteolin, apigenin, vitamin C and kuwanon C. n-hexane extract of Morus nigra at dose of 250 mg/kg reduced elevated ALT by 54.3% (p<0.001), AST by 55.1% (p<0.01), ALP by 28.5% (p<0.01) and TBR by 56.4% (p<0.01) as compared to paracetamol control. The dose of 500 mg/kg of the extract reduced the ALT levels by 62.9% (p<0.001), AST by 56.7% (p<0.01), ALP by 33.6% (p<0.01) and TBR by 54.5% (p<0.01), as compared to paracetamol group. However, the reduction of liver enzymes and total bilirubin after administration of extract was comparable to the silymarin. Current study demonstrated potential hepatoprotective activity of n-hexane extract of Morus nigra.